Increasing referral rate for screening colonoscopy through patient education and activation at a primary care clinic in New York City. Issue 8 (August 2016) - Sriphanlop, Pathu; Hennelly, Marie Oliva; Sperling, Dylan; Villagra, Cristina; Jandorf, Lina
Highlights: Two low-cost interventions aimed at increasing colonoscopy referrals were developed. Referral rates increased by 20–27% when patients were given a handout and/or health counseling. More patients who received the intervention also brought up colonoscopy with their doctors. Results indicate that both interventions are effective at increasing colonoscopy referrals. Abstract: Objective: Colorectal cancer could be prevented through regular screening. Individuals age 50 and older are recommended to get screened via colonoscopy. Because physician referral is a major predictor of colonoscopy completion, two low-cost, evidence-based interventions were tested to increase referrals by activating patients to self-advocate. Methods: This study compared the impact of a pre-visit educational handout that prompts patients to discuss colonoscopy with their physician with the handout plus brief counseling through exit interviews and chart reviews. The main outcome was physician referral. Results: Medical charts were reviewed for eligibility: 130 control patients (Arm 1), 45 patients who received the educational handout and health counseling (Arm 2), and 50 patients who received only the handout (Arm 3). Colonoscopy referral rates increased from 24.6% in Arm 1 to 44.4% and 52.0% in Arms 2 and 3, respectively ( p  = 0.001). The proportion of exit interview participants who discussed colonoscopy with their doctor increased from 68.8% in Arm 1 to 76.5% and 88.9% in Arms 2 and 3, respectively. Conclusions: Results indicate that both interventions are effective at increasing colonoscopy referrals. Practical implications: : Results suggest that an educational handout alone is sufficient in prompting patient-initiated discussions about colonoscopy.